2023
DOI: 10.1186/s12889-023-15201-0
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers in the development and implementation of depression prevention and treatment policies in China: a qualitative study

Abstract: Background Depression is one of the leading causes of avoidable suffering and premature death worldwide, leading to the disease burden among mental disorders. Depression-related deaths can be prevented by developing and implementing good depression prevention and treatment policies. The goal of this study is to provide theoretical direction and useful references for examining the outstanding service work of depression prevention and treatment. It also aims to describe how depression prevention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Conversely, Zhuang women with a family history of mental illness were less likely to seek help, likely due to the stigma attached to mental disorders an concerns about preserving family honor [48][49][50][51][52]. Accordingly, there is an urgent need for educational campaigns and policies that promote the reduction of pervasive stigma against individuals with mental disorders through various means such as utilizing mass media effectively and implementing awareness-raising interventions [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Zhuang women with a family history of mental illness were less likely to seek help, likely due to the stigma attached to mental disorders an concerns about preserving family honor [48][49][50][51][52]. Accordingly, there is an urgent need for educational campaigns and policies that promote the reduction of pervasive stigma against individuals with mental disorders through various means such as utilizing mass media effectively and implementing awareness-raising interventions [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the Action Plan to Develop Specialized Services for the Prevention and Treatment of Depressive Disorders [ 128 ] in China is a significant policy in the progress of mental health services. However, to implement the Plan, several major challenges need be addressed, such as lack of resources, lack of united action, and insufficient awareness of depression [ 129 , 130 ]. Thus, prevention and treatment for depression, especially the improved access of services is a long-term process cross low-income and middle-income countries [ 131 ], including China [ 129 , 130 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, to implement the Plan, several major challenges need be addressed, such as lack of resources, lack of united action, and insufficient awareness of depression [ 129 , 130 ]. Thus, prevention and treatment for depression, especially the improved access of services is a long-term process cross low-income and middle-income countries [ 131 ], including China [ 129 , 130 ].…”
Section: Discussionmentioning
confidence: 99%
“…4,14 From this perspective, the depressive tendency is important. Meta-analyses have shown that previous studies have mainly defined depressive tendencies based on three aspects: (1) individuals have at least one or two core symptoms of MDD (such as depressed mood or loss of interest), accompanied by one or more other symptoms of MDD, but do not meet all the criteria for MDD, as well as other specific criteria; (2) high scores on self-reported measures of depression, such as at least 16 points on the Centre for Epidemiological Studies Depression Scale (CES-D); (3) The duration of individual corresponding symptom manifestations is 1-2 weeks. 4,15 However, there is still a lack of unified standards and definitions for depressive tendencies.…”
Section: Concept Of Depressive Tendencymentioning
confidence: 99%
“…To promote the mental health of adolescents, the Chinese government has released multiple policy documents in recent years, proposing to prioritize the prevention and treatment of depression. 1 In 2021, the Ministry of Education explicitly incorporated depression screening into the health examination content for students. Depressive tendency is regarded as an initial stage in the development of depression.…”
Section: Introductionmentioning
confidence: 99%